Production of mannanase from palm kernel cake by Bacillus subtilis ATCC 11774 and purification using aqueuos two-phase systems - Mahamad Norizan, Nor Amalina (2019)
Palm kernel cake (PKC) is an agro-industrial by product from the palm oil extraction, which constitutes about 50% of the original oil palm (Elaeis guineensis) kernel. PKC has high protein content and essential amino acids, which has potential to be used as a protein source. However, PKC is normally not being used as a 100% feed especially in poultry, fish and other monogastric animals due to its low protein digestibility, high fibrous, poor texture, low palatability and gritty nature. The use of multi-carbohydrase enzymes, especially mannanase, would overcome these problems because mannan contributes the large portion of PKC. The objective of the present study was to investigate and optimized the fermentation process for β-mannanase production by Bacillus subtilis ATCC 11774 using PKC as substrate and also to develop the recovery process of the enzyme from the fermentation broth. The production of mannanase was studied in shake flask culture and the optimization of medium composition was performed based on the modified composition of nutrient broth(NB). A full factorial central composite design (CCD) was applied to further optimize the significant variables which were selected from Plackett-Burman screening design. In the CCD, the three factors (PKC, peptone and NaCl) were selected and tested in twenty fermentation runs. A polymer–salt aqueous twophase system consisting of polyethylene–glycol (PEG) with sodium citrate was developed for direct recovery of a β-mannanase from a culture of B. subtilis ATCC 11774, which produced an extracellular β-mannanase (805.12 U/mL) under submerged fermentation (SmF) using palm kernel cake as the substrate. The partition behavior of B. subtilis ATCC 11774 β-mannanase was investigated with various parameters, which include phase composition, tie-line length (TLL), volume ratio (VR), sample loading and system pH. Response surface curve showed that the increase in PKC concentration, peptone and NaCl would lead to an increase in β-mannanase production to the optimum value of 805.12 U/mL. Statistical optimization from fermentation process using response surface methodology (RSM) successfully increase the production of β-mannanase. Under optimum conditions of ATPS, the purification of β-mannanase was achieved at PEG 4000-sodium citrate system using TLL of 41.15% (w/w), with VR of 0.58 at pH 5.5 for 10% (w/w) crude load where the β-mannanase preferentially partitioned into bottom salt phase. Based on this system, the purification factor of β-mannanase was enhanced to 3.83-fold, with a yield of 98.61% recovery. Second stage ATPS with fresh bottom phase further improved purification of β-mannanase to 12.42-fold with 345.18 U/mL specific activity. Given that the operation of aqueous two-phase systems is simple, environmentally friendly and cost-effective, as it requires only salts and PEG, it may have potential for industrial applications in the purification of β-mannanase from fermentation broth.